Tidelands - Gregory, Philippa (Atria Books, 2019)
Midsummer's Eve, 1648, England is in the grip of civil war between renegade King and rebellious Parliament. The struggle reaches to every corner of the kingdom, even the remote Tidelands - the marshy landscape of the south coast. Alinor a descendant of wise women, crushed by poverty and superstition, waits in the graveyard under the full moon for a ghost who will declare her free from her abusive husband. Instead, she meets James, a young man on the run and shows him the secret ways across the treacherous marsh, not knowing that she is leading disaster into the heart of her life. Suspected of posessing dark secrets in a suspicious country, Alinor's ambition and determination marks her out from her neighbours. But this is the time of witch-mania, when it is dangerous for a woman to be different....